Columbian Sharp-tailed Grouse reintroduction to Middle Park - Richert, Josh, speaker; Kossler, John, speaker; Riley, Terry, moderator; International Wildlife Ranching Symposium, producer (Colorado State University. Libraries, 2014)
The Columbian Sharp-tailed Grouse (Tympanuchus phasianellus columbianus; CSTG) is the rarest of six sub-species of grouse that are endemic to sagebrush, shrubsteppe and mountain shrub communities of western North America. It currently occupies less than 10% of its historic range, including 3 counties in northwestern Colorado, due to habitat loss, energy development, changes in land management and urban expansion. CSTG populations had been documented in the Lower Blue River Basin of Middle Park in North-Central Colorado as recently as the mid-1950s, so a cooperative effort between Colorado Parks and Wildlife (CPW) and private landowner Blue Valley Ranch (BVR) sought to re-introduce the bird to this area. Trapping occurred from the Fall 2006 - Spring 2008 seasons in the Hayden and Craig areas of Northwestern Colorado. A total of 91 females and 58 males were released on Blue Valley Ranch from 2006 - 2008. Approximately 15 males and 27 females were deployed with VHF radio transmitters for monitoring. Habitat and nesting data were also collected for comparison with the trapping area. Since the release, two permanent leks have been established with high counts of 21 and 26 males in 2014, with two additional lek sites needing confirmation in 2015. The project has been successful in establishing a new population of CSTG on a private, 25,000 acre conservation ranch within their historical range, and CPW plans to augment the population with additional CSTG releases over the next 2-3 years in the Williams Fork Drainage, about 8 miles east of BVR.
Sharp-tailed grouse reintroduction projects on Blue Valley Ranch
Moderator: Terry Riley.
Presented at the 8th international congress for wildlife and livelihoods on private and communal lands: livestock, tourism, and spirit, that was held on September 7-12, 2014 in Estes Park, Colorado.
Video presenter: Josh Richert.
To request a transcript, please contact library_digitaladmin@mail.colostate.edu or call (970) 491-1844.
Keywords: Wildlife management -- Congresses; Range management -- Congresses